Flowering and fruiting seasonal changes of six accessions of Jatropha curcas L. in a semi-arid region of Senegal - Diedhiou, Ibrahima; Bayala, Roger; Sagna, Moustapha Diere; Madiallacke, Diedhiou Pape (Journal of Natural History Museum, 2018)
Jatropha curcas is the priority species for biofuel promotion in Senegal. However the lack of knowledge on floral biology and fruiting of this plant remains a problem to increase its yield and improve farmers’ adoption. The objectives of this study were to assess seasonal changes on flowering and fruiting of six accessions of Jatropha curcas in semi-arid area, Senegal. In this study the total number of inflorescences, flowers and fruits were evaluated during six month son four years old plants, installed in the Agricultural Engineering School ( ENSA) of Thies. The results showed significant effect of the studied factors (season, accession) and interaction between them on floral and fruiting traits of J. curcas. Due to more favorable climatic conditions, the performance of flowering is better in the wet season. During this season, the number of male and female flowers ranged, respectively from 107.47–191.60 and from 2.47–11.87 per inflorescence. Consequently, ripe fruits production was higher in wet season and varied between66 and 97% of the total production. Two peaks of flowering were observed; the first one occurred in dry season (April, 24th- June 6th) and the second, with the highest number of inflorescences, arrived in wet season (8 - 22 July). Fruiting patterns is highest concentration between at the end of the wet season (September 15th and October 3rd).High seed yields were observed with the accessions CE6 (2739.3 kg ha-1), CE97 (1451.0 kg ha-1) and CE95 (1326.3 kg ha-1) that are promising for biofuel production in semi-arid areas of Senegal.